Analisis Kelimpahan Fitoplankton dan Zooplankton di Sungai Batang Hari di Kabupaten Tebo - Adriansyah, Endi; Suzana, Asih; Marhadi, Marhadi; Amini, Fadilah; Sufra, Rifqi (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to analyze the structure of plankton abundance and water quality in the Batang Hari River in Tebo Regency. The research method used was purposive sampling at 3 (three) points on the Batang Hari River during February - July 2024. The research results found 3 classes of Phytoplankton, namely: Bacillariophyceae, Chlorophyceae, and Cyanophyceae as well as 1 species of Zooplankton (Ciliata). This research also found the Shannon-Wiener diversity index (H') between 1.555 and 1.559; This shows the moderate stability of the plankton community and is supported by a water temperature of 28°C and adequate phosphate and nitrate content.